The Role of Task-Technology Fit on the Design and Use of a Hotel Management System - Dzikria, Intan; Solihin, Muhammad Lutfi Syahindra (Journal of Information Technology and Cyber Security, 2023)
Hotels have many problems regarding how to improve their service performance by using technologies, especially when the hotels have a bit of understanding the importance of their employees’ tasks and the technology fitness. This study designed a hotel management system based on the tasks that the employees use to provide services. The purpose of this research is to investigate the influence of task-technology fit on the intention to use the designed hotel management system. In addition, statistical testing methods are also carried out on the system by measuring the impact of task-technology fit on the suitability between user task needs and technology, on user perceptions of technology and how these perceptions affect user intentions and behavior in accepting and using technology. The results of this study indicate that task-technology fit has a significant impact in facilitating its use. The results of this study contribute to the academic implementation of task-technology fit theory in the hotel reservation management system.